Combined strategy for removal of Reactive Black 5 by biomass sorption on Macrocystis pyrifera and zerovalent iron nanoparticles - García, Fabiana Elena (2018)
Reactive Black 5, RB5, has been used as a model azo dye to evaluate the removal efficiency of sorption on Macrocystis pyrifera biomass (Mpyr) and commercial zerovalent iron nanoparticles (nZVI) in individual and combined treatments. The best conditions for the treatment with the isolated materials were first determined, and then, in series and combined treatments were performed under these conditions, achieving removal efficiencies higher than 80% of the initial dye concentration. Strengths and weaknesses of all removal strategies (individual, in series and combined) are analyzed regarding the application on real effluents. Mpyr efficiently adsorbed RB5, but also increased the total organic content by partial dissolution of components of the algal biomass. Removal experiments with commercial nZVI were also efficient but liberated Fe to the solution, and sulfanilic acid was observed after the treatment as a product of RB5 degradation. In contrast, after the Mpyr treatment, no sulfanilic acid was detected, suggesting that sulfanilic acid is efficiently adsorbed by the biomass. The best condition was the integrated use of Mpyr and nZVI, with a remarkable removal efficiency (69–80%) obtained after only 1 h of treatment. Finally, nZVI were successfully immobilized in Mpyr, and the hybrid material was used to remove RB5 in continuous flow experiments at pH 3, obtaining a removal capacity of 39.9 mg RB5 g−1 after a total processed volume of 630 mL of [RB5]0 = 100 mg L−1.